Expanding the clinical spectrum of interleukin-2 receptor alpha chain deficiency: two novel cases with long-term hematopoietic stem cell transplantation outcome and literature review - Alzubedy, Maha; Osman, Ahmed Sayed; Alajlan, Huda; Alazami, Anas M; Al-Mousa, Hamoud (Frontiers in Immunology, 2026)
BackgroundInterleukin-2 receptor alpha chain (IL2RA, CD25) deficiency is a rare autosomal recessive inborn error of immunity characterized by profound immune dysregulation, susceptibility to infections, and autoimmunity. Only 13 cases of IL2RA deficiency have been reported worldwide since its first description in 1997, and experience with allogeneic hematopoietic stem cell transplantation (HSCT) for this condition remains very limited. This study aimed to describe the clinical, immunological, genetic, and HSCT outcomes of two siblings with IL2RA deficiency with a novel homozygous frameshift mutation and to review previously reported cases.MethodsThe clinical course, laboratory findings, genetic diagnosis, and transplant outcomes of two patients managed at King Faisal Specialist Hospital & Research Centre were retrospectively reviewed. A comprehensive literature review was conducted to contextualize these cases.ResultsBoth patients presented with severe enteropathy, eczema, recurrent respiratory infections, growth failure, and features of allergic disease in early childhood. Immunological evaluation revealed hypergammaglobulinemia, impaired T-cell proliferation, reduced CD19+ B cells, inverted CD4/CD8 ratio, and absence of CD25 expression. Genetic analysis revealed a novel homozygous frameshift variant in IL2RA (c.166delC; p.R56fs). Both patients underwent HSCT with myeloablative conditioning. The younger sibling received marrow from a matched unrelated donor and achieved full donor chimerism with complete clinical and immunological recovery, remaining well 6 years after HSCT. The older sibling received marrow from a matched related donor and is alive and stable at 5 years of follow-up, with sustained donor chimerism and resolution of autoimmunity, complicated only by transient mild chronic graft-versus-host disease.DiscussionThe two cases expand the mutational and clinical spectrum of IL2RA deficiency and provide long-term evidence that HSCT can cure immune dysregulation and susceptibility to infection. The findings underscore the importance of early genetic diagnosis and timely consideration of HSCT as definitive therapy for this rare but life-threatening disorder.